Evaluación de tres niveles de fitasa en dietas de cerdo en la etapa de crecimiento en el cantón Vinces, Los Ríos - Luna Zambrano, Karen Antonella (2024)
This study aims to evaluate the effect of three levels of phytase in the diet of growing pigs in Vinces, Los Ríos. A completely randomized design was used with 12 pigs of Duroc x Pietrain cross, and three levels of phytase were assessed: 0.1% (T1), 0.15% (T2), and 0.2% (T3), compared to a control group without phytase (T0). The study was conducted over 35 days during the growth stage, analyzing variables such as feed consumption, daily weight gain, feed conversion ratio, and benefit/cost ratio. The results showed that although there were no significant differences in feed consumption among treatments, the highest phytase level (T3) exhibited the highest numerical feed consumption. Regarding daily weight gain, T3 resulted in a significantly higher gain, with 6.13 kg in the fifth week, compared to other treatments. Feed conversion was also more efficient in the T3 group, reaching a conversion rate of 2.67 g/g, although differences among treatments were not statistically significant. Economically, T3 provided the best benefit/cost ratio, with a benefit of 1.26, indicating that higher levels of phytase supplementation not only improve productive performance but also economic profitability. The conclusions suggest that including phytase in the diet of pigs significantly enhances weight gain and feed conversion, with the 0.2% level being the most effective in both productive and economic terms. It is recommended to use this level of phytase to optimize efficiency in pig production and to conduct further studies under different climatic conditions to validate these results and adjust supplementation as needed.